Demand side management using direct load control for residential - Majid, M. S.; Rahman, Hasimah Ab.; Hassan, M. Y.; Ooi, Chia Ai (2006)
Dramatic increase in the number of domestic consumers due to mass electrification will have implications for the national generation, transmission and distribution. The nature of the domestic load coincides with the evening peak which is more expensive to generate. This indicates the need for Demand Side Management (DSM) in residential as a strategy to reduce the impact of domestic peaks on the national electricity load and related costs. This paper describes the software development written in Visual C++ 6.0 to control directly the residential loads through communicating with parallel port. Graphic User Interface (GUI) was designed for the software. Comparison was done between load curve without controller and with controller. The result shows a reduction in energy consumption with the application of DSM controller. Hence, DSM application improves the management of both power and energy consumptions.